Safety and effectiveness of chloral hydrate in outpatient paediatric sedation for objective hearing tests. (November 2019) - Necula, Violeta; Stamate, Mirela Cristina; Blebea, Cristina; Cozma, Sebastian
Abstract: Objectives: Chloral hydrate is a sedative that has been used for many years in clinical practice and, under proper conditions, gives a deep and long enough sleep to allow performance of objective hearing tests in young children. The reluctance to use this substance stems from side effects reported over time that can vary, depending on dose, procedure settings and immediate life supporting intervention when needed. Our study adds to those that have appeared in recent years, showing that chloral hydrate is an effective and safe substance when is used in proper conditions. Methods: The study included 322 children who needed sedation for objective hearing tests, from April 2014 to March 2018. Parents were instructed to bring the child tired and fasted for at least 2 h before sedation. The sedative was administered by trained staff in the hospital, and the child was monitored until awaking. Results: In our study group, over half of the children were in the age 1–4 years group, and only 15% were older than 4 years. The dose of chloral hydrate ranged between 50 and 83 mg/kg body weight, with an average of 75 mg. Successful sedation occurred in 94.1% of children; 0.9% of children awoke during testing and required supplemental sedation or rescheduling of the testing. The most common side effects were vomiting, agitation, prolonged sleep, and failure to fall asleep. Conclusions: Comparing the side effects of chloral hydrate in our study with those from other studies, ours were similar to those described in the literature. In our study chloral hydrate was effective and had only limited adverse effects. The use of chloral hydrate under hospital conditions with proper monitoring could be a practical and safe solution for outpatients or those with short-term hospitalisation.